PREDIKSI TINGKAT PERKAWINAN ANAK BERBASIS FUZZY UNTUK MEMINIMALISASI DAMPAK PASCA PERKAWINAN - Ashari, Ayu; Setiawan, Aries; Ratnawati, Juli; Wulandari, Fitria; Farida, Ida; Prasetya, Jaka; Hallang Lewa, Andi; Suharnawi, Suharnawi (Dian Nuswantoro Semarang, 2024)
Early marriage is a global problem in the world, one of which is Indonesia. Based on data obtained from the Central Statistics Agency in 2020, Central Java is one of the 3 provinces in Indonesia which has the highest child marriage rate, namely 10.85%. Child marriage will have a negative impact on both married teenagers, their families, schools, communities and the country. The government has made efforts to change the legal regulations regarding the minimum age for marriage, namely 19 years, but there are still many teenagers who marry early at less than 19 years with the existence of a marriage dispensation. Efforts are needed to help the government to prevent an increase in child marriage rates and make the RPJMN a success. This research aims to find out accurate predictions about the level of child marriage through a system that can produce accurate data. The methodology used in this research is fuzzy which has been proven to be a good method for carrying out predictive analysis. The accuracy value resulting from trials using the fuzzy method was 90%.